Indonesian Bankruptcy Law From A Sociological Jurisprudence Perspective - Alfin Sulaiman; Siti Nurbaiti; Anna Maria Tri Anggraini (Rechtsnormen: Journal of Law, 2026)
Background. Indonesian bankruptcy law under Law Number 37 of 2004 is formally designed as a technical mechanism for collective debt settlement, yet its application operates within a socio-cultural context that perceives insolvency as a moral failure and social stigma. Purpose. This study aims to analyze how Indonesian bankruptcy law functions as an instrument of social engineering when examined through the perspective of sociological jurisprudence, particularly in balancing creditor rights, business continuity, and broader socio-economic stability. Method. The research employs a normative legal method using statutory and conceptual approaches. Primary legal materials include bankruptcy legislation and relevant judicial decisions, while secondary materials consist of doctrinal writings on sociological jurisprudence and insolvency law. Results. The study finds that the suspension of debt payment mechanism contributes to the preservation of the social function of business entities by enabling courts to prioritize restructuring over liquidation, thereby supporting employment protection and macroeconomic stability. In practice, this is reflected in judicial tendencies to emphasize going concern considerations and consensual settlement during PKPU proceedings. Conclusion. This study offers a novel contribution by systematically positioning bankruptcy law as a form of institutionalized social engineering, demonstrating that integrating sociological considerations into judicial interpretation and normative reform is essential for transforming bankruptcy law from a liquidation-centered mechanism into a constructive instrument for economic resilience and social justice.